Case of Vengeful Woman in News Text: Sara Mills' Critical Discourse Analysis - Alhabiib Josy Asheva; Aulia Zahra Tasyarasita (Deiksis, 2022)
Women are frequently underrepresented in the media and its content gives more favors to men. The discussion of the portrayal of women in news media cannot be separated from the values and ideology of a journalist. This paper aims at investigating the position of the subject, object, and reader, also identifying the ideology of the author on the news article. This research applied the descriptive qualitative approach. The data source of the research is in the form of vocabularies, phrases, or sentences that reflected Sara Mills’ model in a news text entitled Indonesian Woman Sends Poisoned Satay to Ex-boyfriend, Ends up Killing Delivery Man's Son instead obtained from asiaone.com published in May 04, 2021. The findings of the research show that the subject position on the news text mostly used noun phrase to refer to the actor. Moreover, for the object position, the author positioned Nani, the actor, as the object. Based on reader position, the use of third person pronoun is majorly used in order to deliver the storyline objectively. The analysis of ideology of the news text revealed that the author does not have any tendency to either marginalize or defend the woman